Cervical Cancer Screening: Defining the Need for Research - Simoes, E.; Brucker, S.; Beckmann, M. W.; Ortmann, O.; Albring, C.; Wallwiener, D. (Geburtshilfe und Frauenheilkunde, 2013)
With the development of a National Cancer Plan published in 2012, Germany has followed the recommendations of the WHO and the EU. The first area of action listed in Germanyʼs National Cancer Plan is improving the early detection of cancer. Both citizens and medical specialists are encouraged to take responsibility themselves and contribute to the efforts being made to meet the challenge of cancer. Screening for cervical cancer has long been an integral part of the German Directive for the Early Detection of Cancer and now – following the recommendations given in the European Guideline – an organised screening approach shall be developed to maximise the benefits and minimise the risks through a partial reorganisation of existing structures. Before this can be rolled out nationwide, it will be necessary to check the feasibility and suitability of new contents and organisational structures. The Federal Joint Committee which is largely responsible for the process according to the draft law on the implementation of the National Cancer Plan has emphasised the importance of evidence-based medicine and of collaboration between the autonomous governing bodies within the healthcare system to obtain viable results. For medical specialists, the follow-on question is which areas will need more research in future. New process steps need to be developed and verified to see whether they offer evidence which will support defined approaches or whether such evidence needs to be newly compiled, e.g. by testing invitation procedures for screening in trial schemes. The experience gained during the implementation of the existing directive on early detection of cancer should be integrated into the new process. Research initiated by specialists could encourage the development of a new version of the Directive for the Early Detection of Cancer suitable for the Germanyʼs healthcare system.
Keywords: cervical cancer; cervical intraepithelial neoplasia (CIN); gynaecology; screening